Targeted whole genome sequencing protocols for African and classical swine fever viruses - McDowell, Chester Dale (My University, 2025)
The increasing availability and feasibility of sequencing has facilitated the advancement of infectious disease research including pathogen discovery, phylogenetic characterization, and viral evolution. Sequencing data combined with clinical disease, virulence, and viral dynamics data, can reveal a more complete understanding of viral evolution for the development of novel and effective control measures. Furthermore, experimental infection studies contribute to our understanding of clinical disease and viral dynamics when there is limited information such as with a novel pathogen or viral strain and provide critical reagents to evaluate the performance of available diagnostics and to develop new ones. African swine fever (ASF) an infectious viral disease caused by African swine fever virus (ASFV) that causes high mortality in domestic swine and wild boar (Sus scrofa). Since the outbreak in 2007 in the country of Georgia, ASFV has continues to spread and remains as a current global threat. In 2019, an African swine fever virus (ASFV) outbreak was reported in Mongolia; due to the limited information from field observations, we conducted an experimental infection of domestic pigs to further evaluate and characterize the progression of clinical disease, virulence, and pathology of an ASFV Mongolia/2019 field isolate (ASFV-MNG19). The study demonstrated that ASFV-MNG19 is a virulent genotype II ASFV strain that causes acute ASF in domestic swine. Controlled experimental studies like this one, are important to evaluate the genetics, virulence and clinical progression of emerging viruses and different variants/strains described in the field, and to aid in the development and validation of diagnostic tools used by regulatory agencies for the rapid detection and implementation of mitigation strategies. Targeted whole genome sequencing protocols are crucial for the rapid identification and complete genetic characterization of emerging and high consequence viral pathogens for outbreak investigations and understanding viral evolution for the development of novel and effective control measures. Such protocols are lacking for two high consequences viral pathogens affecting swine, ASFV and classical swine fever virus (CSFV). In order to fill this gap, we developed independent panels of primers spanning the genomes of ASFV and CSFV to generate approximately 10kB and 6kB amplicons, respectively, providing whole genome amplification. The targeted protocols for these viruses were tested using cell culture-derived viruses and clinical samples generated by our experimental infection studies in swine. These protocols resulted in an average coverage greater than 1000X for ASFV with 99% of the genome covered, and 10,000X-20,000X for CSFV with 97% to 99% of the genomes covered when sequenced on the Oxford Nanopore MinION platform. These protocols will be important tools to assist in early pathogen detection and genetic characterization of these high consequence swine viruses in outbreak and surveillance situations globally and within the United States, should an outbreak occur. Targeted whole genome sequencing protocols were also developed for the emerging zoonotic viral pathogen, SARS-CoV-2, to evaluate the viral competition between ancestral and novel variants in a susceptible host. We conducted a competition experiment whereby adult white-tailed deer (WTD) were co-infected with a lineage A and lineage B alpha variant SARS-CoV-2 isolates. The percent composition of lineage A and B viruses were evaluated using lineage A and B-specific RT-qPCR assays and targeted whole genome sequencing with a BLAST-based analysis. Using the developed protocols, we obtained that the SARS-CoV-2 lineage B alpha variant had improved fitness compared to the lineage A virus in adult WTD. This study demonstrates that sequencing data and bioinformatic pipelines can be used to evaluate strain composition in the presence of a co-infection. The targeted whole genome sequencing protocols developed here can be applied to investigate co-infection competition studies or to evaluate emerging viral variants through single nucleotide variant analysis, providing more information on the viral dynamics and evolution of these high consequence pathogens.
Keywords: African swine fever virus; MinION long read sequencing; Classical swine fever virus; High consequence swine pathogens